Innovation of Interactive Digital Learning Media to Strengthen Business Model Canvas-Based Entrepreneurship Learning Effectiveness - Apprillia Anggraeni Sugiarto; Munawaroh; Nanik Sri Setyani (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Entrepreneurship learning in vocational schools still faces challenges due to low student learning outcomes, primarily caused by the use of monotonous and less interactive learning media. This condition makes it difficult for students to fully understand business planning concepts. This study aims to develop Business Model Canvas (BMC) teaching materials in the form of interactive digital learning media to enhance students’ motivation, conceptual understanding, and learning outcomes in the subject of Creative Projects and Entrepreneurship. The research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consist of material experts, media experts, and 41 students of grade XI in a vocational school, with a product trial involving 15 students. Data were analyzed using quantitative descriptive analysis and the non-parametric Wilcoxon test to determine the effectiveness of the media in improving learning outcomes. The results indicate that the interactive digital teaching materials on the Business Model Canvas topic were rated as highly feasible by experts, practical by teachers and students, and effective in improving learning outcomes, with posttest scores showing an 87.8% increase compared to pretest results. This study concludes that the development of interactive digital teaching materials serves as an innovative solution in entrepreneurship education, fostering engaging, adaptive, and meaningful learning experiences. The implication of this research highlights the importance of systematic integration of digital technology in learning media development to enhance the quality of entrepreneurship education in vocational schools.